PENGARUH PENERAPAN MODEL SURVEY, QUESTION, READ, REFLECT, RECITE, REVIEW (SQ4R) TERHADAP KEMAMPUAN MEMBACA TEKS HIKAYAT SISWA FASE E KELAS X SMA NEGERI 1 LUHAK NAN DUO - Syafnita Lara; Trisna Helda; Ricci Gemarni Tatalia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the following problems. The ability of students to read the text of the story is still very low. Students still have difficulty understanding the content of the story text because the language used is a classic Malay language that they rarely encounter. This study aims to describe the effect of the application of the survey, question, read, reflect, recite, review (SQ4R) model on the ability to read the text of the story of phase E students of SMA Negeri 1 Luhak Nan Duo. This type of research is quantitative research using experimental methods. The design of this study is a posttest-only control design. The population of this study is class X students of SMA Negeri 1 Luhak Nan Duo who are registered in the 2024/2025 school year. The sample in this study was 36 students in class XE-3 (control class) and class XE-4 (experimental class) with 36 students. The sample extraction technique of this study is purposive sampling. The data in this study is in the form of objective test scores based on the indicators of the text of the story. The results of this study can be concluded as follows. First, the ability to read the text of the story without using the survey, question, read, reflect, recite, review (SQ4R) model obtained an average score of 70.56. Second, the ability to read the text of the story using the survey, question, read, reflect, recite, review (SQ4R) model obtained an average score of 82.47. Third, from the results of the data analysis that has been carried out, the use of the survey, question, read, reflect, recite, review (SQ4R) model affects the ability to read the text of the story, this can be seen from the acquisition of Thitung 2.60 is greater than the Ttable 1.99. In other words, the alternative hypothesis (H1) is accepted and has a significant influence.